Ukay’s new groove shared consumption towards clothing reuse through a clothing library and management hub - Moraga, Josiah Samuel B.; Richelle Rhea R. Baria (Quezon City College of Architecture, University of the Philippines Diliman, 2025)
Secondhand clothing (SHC) businesses in the Philippines provide an alternative to fast fashion, yet they remain fragmented and are only reactive to the issue of textile waste. This study explores how shared consumption can revamp the ukay-ukay sector by integrating traditional retail demands and modern sharing economy habits. By reimagining the ukay-ukay typology, this project proposes a complementary program for subscription-based retailers, where customers can borrow clothing to promote re-commerce and minimize linear clothing use. Human-centered design and ecological systems approach are applied by creating an environment that incentivizes participation, artistic experimentation, and discovery, using spatial dynamics that motivate users to actively engage with the clothing library management hub. Key findings attribute ukay-ukay patronage to transparency, grit, flexibility, and artistic expression from which the design concepts of affinitive, gamified, and exchanging arose, followed by its respective design translations. The proposed Tutuban Clothing Library operates on the greater objective of promoting textile waste reduction mainly by providing a platform for shared consumption, resource efficiency, and self-exploration in the fashion of the masses. The potential of architecture to influence behavior by making circular fashion more accessible and desirable was realized during the process of this study. Ultimately, the project offers a precedent for generating new insights and further research into crowd-oriented approaches in sustainable fashion infrastructure.
Include appendices
Thesis (Bachelor of Science in Architecture) -- University of the Philippines Diliman
Keywords: Tutuban Clothing Library; Used clothing industry -- Philippines; Textile waste -- Philippines; Circular economy -- Philippines